Moderasi Beragama Sebagai Katalisator Untuk Kohesi Sosial Di Desa Puntukdoro Magetan - Maksum, Muh; Priamono, Gilang Hardiansyah; Mansyuri, Aulya Hamidah; Arifa’i, Muhammad Andiyan (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study explores religious moderation as a catalyst for enhancing social cohesion in Puntukdoro Village, where intolerance towards Christians poses a significant challenge. Data were obtained from primary sources through structured interviews, observations, and documentation, as well as from secondary sources in the form of relevant documents. The data analysis techniques used include data reduction, presentation of data in narrative form, and drawing conclusions. Activities include the